2015
DOI: 10.1371/journal.pbio.1002073
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Hierarchies Perform Bayesian Causal Inference in Multisensory Perception

Abstract: To form a veridical percept of the environment, the brain needs to integrate sensory signals from a common source but segregate those from independent sources. Thus, perception inherently relies on solving the “causal inference problem.” Behaviorally, humans solve this problem optimally as predicted by Bayesian Causal Inference; yet, the underlying neural mechanisms are unexplored. Combining psychophysics, Bayesian modeling, functional magnetic resonance imaging (fMRI), and multivariate decoding in an audiovis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
316
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 288 publications
(363 citation statements)
references
References 48 publications
(50 reference statements)
23
316
3
Order By: Relevance
“…The latter will be determined by the type of sensory feature representation, as well as by prior knowledge and goals. The development of new theoretical and mathematical approaches (e.g., Bayesian causal inference, Rohe and Noppeney, 2015a) will help us with the interpretation of these neuronal effects. In addition, I believe that together with sophisticated and well-controlled experiments, it is important to look also into more naturalistic and life-like multisensory conditions.…”
Section: Unmentioning
confidence: 99%
“…The latter will be determined by the type of sensory feature representation, as well as by prior knowledge and goals. The development of new theoretical and mathematical approaches (e.g., Bayesian causal inference, Rohe and Noppeney, 2015a) will help us with the interpretation of these neuronal effects. In addition, I believe that together with sophisticated and well-controlled experiments, it is important to look also into more naturalistic and life-like multisensory conditions.…”
Section: Unmentioning
confidence: 99%
“…Multi-voxel pattern analysis (MVPA) represents an opposite way of modeling, trying to predict stimulus categories using an entire hemodynamic activation pattern, without being restricted to an assumption of certain predefined response function or stimulus model (Norman et al 2006, Pereira et al 2008, Mur et al 2009). By enabling classification of complex stimulus-specific activation patterns even in the absence of regional amplitude changes, MVPA provides a powerful new approach to investigate the mechanisms of audiovisual integration (Pooresmaeli et al 2014, Gentile et al 2015, Li et al 2015, Rohe & Noppeney 2015. For instance, Li et al (2015) recently found distributed content-specific (male vs. female, crying vs. laughing) supratemporal activations during audiovisual perception of faces and voices during selective attention to particular features.…”
Section: Multi-voxel Pattern Analysismentioning
confidence: 99%
“…If not, the system will attempt to reduce this mismatch, or prediction error, by adjusting its prediction about the state of the environment and adapting its generative model for the current context accordingly. Within this scheme, these models are hierarchically structured (Rohe & Noppeney, 2015;Wacongne et al, 2011), where higher levels are capable of capturing patterns in sensory inputs that have larger spatial or temporal spans.…”
Section: Introductionmentioning
confidence: 99%